Vibration analysis of a high-speed rotating GPLRC nanostructure coupled with a piezoelectric actuator - Habibi, Mostafa; Hashemabadi, Davoud; Safarpour, Hamed (European physical journal plus, 2019)
. In this article, the vibration characteristics of high-speed rotating graphene-nanoplatelets (GNP)-reinforced composite cylindrical nanoshell coupled with a piezoelectric actuator (PIAC) are investigated. This composite nanostructure rotates around the axial direction, and the Coriolis and centrifugal effects are considered in the formulation. The material properties of piecewise graphene-reinforced composites (GNPRCs) are assumed to be graded in the thickness direction of the cylindrical nanoshell and estimated through a nanomechanical model. In the current study, the effects of angular velocity, piezoelectric layer, GNPRC and size-effects on the frequency of the spinning GNPRC cylindrical nanoshell coupled with PIAC are studied for the first time. The governing equations and boundary conditions are developed using the minimum potential energy and solved with the aid of generalized differential quadrature (GDQM). In addition, due to existence of piezoelectric layer, Maxwell’s equation is derived. The results show that angular velocity, piezoelectric layer, GNP distribution pattern, length scale parameter and GNP weight function play an important role in the vibrational characteristics of the spinning GNP cylindrical nanoshell coupled with PIAC. The results of the current study are useful for design of materials science, micro-electro-mechanical systems and nanoelectromechanical systems such as nanoactuators and nanosensors.